MOBILITAS SOSIAL EKONOMI PENERIMA FASILITAS KREDIT KOPERASI PRIMER ANGGOTA (KKPA) DI DESA DANAU LANCANG KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - LIDUN "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine the socio-economic characteristics of the receiving facility KKPA on Lake Village Unit Lancang Beautiful (KUD Dalin) and to explain the socio-economic mobility recipients creditor and creditor to explain management patterns that affect the socio-economic mobility creditor receiving facility at Lake Village Unit Cooperatives Beautiful sassy.Data analysis techniques used in this research is descriptive quantitative techniques. The research was conducted in the village of Lake Lancang, District Tapung Hulu, Kampar with the entire peasant population is receiving facility Primary Cooperatives Members in KUD Dalin with samples taken 54 0rang (10% of the population) by using simple random sampling method. The data used are primary data and secondary data and analyzed using descriptive analysis.Based on the survey results revealed that the Member Primary Cooperative Credit program (creditor) is applied to the KUD Dalin public comment with a response that is able to improve the socio-economic KKPA farmer members and it is also demonstrated an increase in vertical social mobility. Then the farmer response to the application of a creditor at KUD Dalin was very good, although the earned income credit tends to still low but can be completed on time. The reason farmers cooperatives Dalin using Primary Cooperative Credit facilities Member (creditor) Since there is no capital that need assistance to get the garden Cooperative PT in partnership with intermediaries and help the bank as executor partnership. Judging from the socio-economic mobility of farmers who receive credit facilities Primary Cooperative Members (creditor) occurs vertical mobility and evidenced by improvements in the level of well-being such as increasing the number of permanent homes, kepemilkan land, and an increase in the ownership of other assets.Keywords: Pattern creditor, Social Mobility.